NUTRITIONAL VALUE AND BIOLOGICAL ACTIVITY OF K. ALVAREZII GROWN IN INTEGRATED MULTI-TROPHIC AQUACULTURE - R.A. Islamy,; V. Hasan,; Sze-Wan Poong,; Y. Kilawati,; A.P. Basir,; A.S. Kamarudin, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to assess the nutritional value, phytochemical composition, and antioxidant activity of Kappaphycus alvarezii cultivated in Integrated Multi-Trophic Aquaculture (IMTA) systems. The parameters were nutritional components, phytochemical content, and aAntioxidant activity. K. alvarezii exhibited substantial nutritional value, with notable protein (15.3%) and carbohydrate (60.0%) content, along with essential minerals such as calcium and magnesium. Phytochemical analysis revealed significant levels of polyphenols (20.0 mg GAE/g), flavonoids (5.5 mg QE/g), and tannins (3.0 mg CE/g), as well as noteworthy saponin (1.2%) and alkaloid (0.9%) contents. Antioxidant assays demonstrated strong activities, with 80.2% DPPH and 70.5% ABTS radical scavenging, a FRAP value of 600 µmol Fe2+/g, and a total antioxidant capacity of 150 mg AA/g. The findings indicate that K. alvarezii from IMTA systems is a valuable source of nutrients and bioactive compounds with significant antioxidant properties.